A taxonomic revision of the genus Metadrinomyia Shima (Diptera: Tachinidae) with descriptions of two new species - Byun, Hye-Woo; Han, Ho-Yeon (Zootaxa, 2009)
A little known tachinid genus, Metadrinomyia Shima, is revised based on four East Asian species including two new to science: M. flavifrons sp. nov. and M. xanthokolos sp. nov. The majority of the specimens used in this study were collected from low vegetation in the foothills of mountains in South Korea. The new species can be clearly distinguished from their congeners by their pruinosity, chaetotaxy and genitalic structures. A key, descriptions, photographs, and illustrations of the male genitalic structures are provided and the phylogenetic relationships among the species are investigated.